Structure formation in binary systems hydrolysis lignin – oil product and thermochemical transformations of composites on their basis - Reznikov, Ivan V.; Savitskaya, Tatyana A.; Grinshpan, Dmitry D. (Journal of the Belarusian State University. Chemistry, 2020)
Rheological properties of hydrophobized hydrolysis lignin dispersions in tank oil, diesel fuel, and industrial oil were under study. It was found that at the hydrolysis lignin content of more than 20 wt. %, a coagulation-thixotropic structure with a pseudoplastic flow pattern is formed. The parameters of structure formation calculated within the theory of elastic flocks made it possible to characterize dispersions in diesel fuel as least structured. In accordance with the theory of diffusion-limited aggregation, a computer model of the aggregate of hydrolytic lignin particles in diesel fuel was calculated and its internal structure was established using the proposed method of computer analysis of digital photographs. Machine learning was used to predict the optimal conditions for the production of mesoporous activated carbons from hydrolysis lignin. Experimentally obtained carbons are characterized by total pore volume of (0.95 ± 0.05) cm3/g and BET surface area of (1700 ± 85) m2/g, that corresponds to the predicted parameters.
Keywords: hydrolysis lignin; oil products; structure; machine learning; activated carbon; rheology